Combating Corruption in Nigeria: A Case Study of Public Prosecution under Buhari’s Administration (2015-2023) - Okechukwu, Esther Kalu; Aderinto, Amidu Opeyemi; Lawal, Sultan Babatunde (African Journal of Stability and Development (AJSD), 2024)
The menace of corruption in Nigeria has lingered on for years, the conscious awareness towards this malady has gained prominence over the years, to the extent that the main opposition party, All Progressive Congress (APC), ascended to power in the 2015 General Elections, emerging victorious at the polls with anti-corruption campaign, echoed by the change mantra. This study dissected the much-anticipated fight against corruption in the eight years of Muhammadu Buhari’s APC led administration; it unravels that the principle The menace of corruption in Nigeria has lingered on for years, the conscious awareness towards this malady has gained prominence over the years, to the extent that the main opposition party, All Progressive Congress (APC), ascended to power in the 2015 General Elections, emerging victorious at the polls with anti-corruption campaign, echoed by the change mantra. This study dissected the much-anticipated fight against corruption in the eight years of Muhammadu Buhari’s APC led administration; it unravels that the principle of rotation of power with its patron-client network and identity politics are enablers of corruption in Nigeria. Similarly, it is posited that plea bargain constitutes a huge hindrance to the successful eradication of corruption in Nigeria, just as the poor reward system for career public office holders constitutes a challenge to the fight against corruption in Nigeria. The study concluded that the Buhari administration’s fight against corruption, although had Nigerians filled with hopes from inception, could not achieve much in the end with the anti-corruption Caesar (Ibrahim Magu) removed in what appears as a power play. We recommend the establishment of institutional mechanisms to prevent corruption, review of reward system for public officers, creation of credit system to facilitate citizens’ immediate access to meeting their needs, prosecution of civil/public servants who are complicit in corrupt practices, and compensation of whistleblowers, among other measures.